Correlation Analysis Between Serum Uric Acid, Prealbumin Level, Lactate Dehydrogenase, and Severity of COVID-19 - Jin, Zhenmu; Zheng, Mo; Shi, Jichan; Ye, Xinchun; Cheng, Fang; Chen, Que-Lu; Huang, Jianping; Jiang, Xian-Gao (Frontiers in Molecular Biosciences, 2021)
Objective: To analyze the correlation between serum uric acid, prealbumin levels, lactate dehydrogenase (LDH), and the severity of COVID-19. Methods: The data from 135 patients with COVID-19 was collected, and the patients were divided into a non-severe group (110 cases) and a severe group (25 cases), according to the severity of illness. Sixty cases with normal physical examinations over the same period and 17 cases diagnosed with other viral pneumonia in the past five years were selected as the control group to analyze the correlation between the detection index and the severity of COVID-19. Results: Serum albumin and prealbumin in the severe group were significantly lower than those in the non-severe group (p < 0.01); serum uric acid in the severe group was lower than that in the non-severe group (p < 0.05). LDH and C-reaction protein (CRP) in the severe group were higher than those in non-severe group (p < 0.01); the levels of albumin, prealbumin, serum uric acid, and LDH in the severe group were significantly different from those in healthy control group (p < 0.01) and the levels of prealbumin, serum uric acid, LDH, and CRP in the severe group were significantly different from those in the other viral pneumonia group (p < 0.01). Serum albumin and prealbumin were positively correlated with the oxygenation index (p < 0.001), while LDH was negatively correlated with oxygenation index (p < 0.001). Conclusion: Serum albumin, prealbumin, the oxygenation index, and LDH are risk factors of COVID-19.